Pengaruh Dukungan Sosial Dan Forgiveness Terhadap Kekerasan Seksual Pada Remaja - Nur Faizah; Layyinah Layyinah (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2015)
This study aimed to determine the effect of social support and forgiveness to sexual violence in adolescent. Samples were victim of sexual violence in social institution under the auspices of the Ministry of Social Affairs in Jakarta, as many as 92 people. There are 3 measuring instrument used in this study, namely Betrayal Trauma Inventory (BTI), Interpersonal Support Evaluation List (ISEL) and Transgression-Related Interpersonal Motivation (TRIM-14). The sampling technique used non-probability sampling. Analysis of the data used multiple regression analysis at 0.05 significance level. Based on the hypothesis testing obtained R2 value of 17.7%. This means that the effect of the independent variable on the dependent variable is equal to 17.7% while 82.3% are influenced by other variables. Based on the sig. obtained sig. 0.002 which means that there is a significant effect of social support (appraisal support, tangible assistance, emotionalsupport, informational support) and forgiveness (avoidance motivation, revenge motivation, and benevolence motivation). DOI: 10.15408/tazkiya.v20i2.9169